PENGARUH PROMOSI, KUALITAS LAYANAN DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PRODUK SKINCARE PADA E-COMMERCE SHOPEE (STUDI PADA MAHASISWA FEB UPNVJ) - Amanda Zahra Wynona (2022)
This study is a quantitative research which purposes to determine the effect of promotion, price and service quality on purchasing decision for Skincare Products in E-Commerce Shopee. This study uses respondent consumers of skincare products namely students at the FEB UPNVJ as a sample and the samples totaled 100 respondents with the probability sampling method using simple random sampling type. Respondent data was collected using a digital questionnaire utilizing the Google Form platform. The data was then analyzed using PLS (Partial Least Square) with the help of SmartPLS 3.0 software. The results indicated that (1) Promotion has a significant effect on purchasing decisions, (2) Service quality has a significant effect on purchasing decisions (3) Price has a significant effect on purchasing decisions (4) Promotion, service quality and price simultaneously have a significant effect on purchasing decisions. Keyword: promotion, service quality, price, purchasing decision, skincare, Shopee